2018
DOI: 10.1088/1755-1315/122/1/012137
|View full text |Cite
|
Sign up to set email alerts
|

Environmental performance, profitability, asset utilization, debt monitoring and firm value

Abstract: The growing issue on firm value shows that firm value is not only determined by the firm ability to increase financial profit, but also by the company's concern in maintaining the environmental condition. The industrial development produces waste that pollutes the environment that has potential to serious impact on the next life. In addition to provide financial benefits, companies are increasingly facing pressure to be socially responsible for the survival of the company. However, past findings demonstrate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 5 publications
0
10
0
5
Order By: Relevance
“…Since its introduction, studies have examined the role of profitability in firm value and investigated this relationship in various sample settings (Chen and Chen 2011;Liow 2010). The literature review in this study revealed conflicting findings of the relationship between profitability and firm value, as documented in (Handoko 2017;Hirdinis 2019;Harahap et al 2020;Ardila et al 2018;Bukit et al 2018;Endri and Fathony 2020). We attempt to examine whether the mixed results for the profitability-firm value relationship can be explained by the dividend policy.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Since its introduction, studies have examined the role of profitability in firm value and investigated this relationship in various sample settings (Chen and Chen 2011;Liow 2010). The literature review in this study revealed conflicting findings of the relationship between profitability and firm value, as documented in (Handoko 2017;Hirdinis 2019;Harahap et al 2020;Ardila et al 2018;Bukit et al 2018;Endri and Fathony 2020). We attempt to examine whether the mixed results for the profitability-firm value relationship can be explained by the dividend policy.…”
Section: Introductionmentioning
confidence: 91%
“…Another study examined the relationship between profitability and firm valuation using data from the Indonesian capital market, and the authors of Chune et al (2018); Cleary (1999); Harahap et al (2020); Ardila et al (2018); Bukit et al (2018); Sutopo and Hananto (2019) proved there was positive evidence of this relationship. For instance, in Ardila et al (2018), whether state ownership enterprises (SOEs) outperform non-SOEs was investigated using a sample of 297 observations from 2012 to 2016.…”
Section: Profitability and Firm Valuementioning
confidence: 99%
See 1 more Smart Citation
“…Tobin'S Q melihat prospek perusahaan dimasa yang akan datang, indikator ini sangat penting diperhatikan untuk mengetahui seberapa besar return yang dapat diterima oleh investor atas investasi yang dilakukannya. Penelitian Bukit et al (2018) menyatakan profitabilitas berpengaruh positif dan signifikan terhadap nilai perusahaan. Sedangkan penelitian yang dilakukan oleh Hirdinis (2019) menyatakan bahwa profitabilitas berpengaruh tidak signifikan terhadap nilai perusahaan.…”
Section: Rata-rata Nilai Perusahaan Sektor Industri Barang Konsumsi Y...unclassified
“…Tanggung jawab sosial tidak hanya dapat meningkatkan manajemen risiko namun juga memberikan perlindungan kekayaan. Kinerja lingkungan yang tinggi dapat memungkinkan mengurangi risiko perusahaan (Bukit et al, 2018;Muhammad et al, 2015). Cai et al (2016) menjelaskan bahwa kinerja lingkungan yang baik dapat membawakan berbagai manfaat kepada masyarakat dan perusahaan.…”
Section: Risiko Sistematisunclassified